Job - Simonetti, Manlio; Conti, Marco (Downers Grove, Ill. : Inter-Varsity Press : IVP Academic, 2014)
"The Book of Job presents its readers with a profound drama concerning innocent suffering. Such honest, forthright wrestling with evil and the silence of God has intrigued a wide gamut of readers both religious and nonreligious." "The excerpts in this collection focus on systematic treatment. Among Greek texts are those from Origen, Didymus the Blind, Julian the Arian, John Chrysostom, Hesychius of Jerusalem and Olympiodorus. Among Latin sources we find Julian of Eclanum, Philip the Priest and Gregory the Great. Among Syriac sources we find Ephrem the Syrian and Isho'dad of Merv, some of whose work is made available here for the first time in English." "In store for readers of this volume is once again a great feast of wisdom from the ancient resources of the church."--Jacket.
General Introduction -- A Guide to Using This Commentary -- Abbreviations -- Introduction to Job Commentary on Job -- Appendix: Early Christian Writers and the Documents Cited -- Biographical Sketches -- Timeline of Writers of the Patristic Period -- Bibliography of Works in Original Languages Bibliography of Works in English Translation -- Author/Writings Index -- Subject Index -- Scripture Index.
Online resource; title from PDF title page (EBSCO, viewed June 27, 2018).
Master record variable field(s) change: 050
Keywords: Bible. -- Commentaries; Bible; RELIGION / Biblical Studies / Old Testament; RELIGION / Biblical Studies / Wisdom Literature; Electronic books; Commentaries